(untitled) (Physical Education, Health and Social Sciences, 2025)
The study explores the multifaceted reasons for the delisting of companies from the Indian stock exchange (Bombay Stock Exchange), with a particular focus on voluntary delisting trends. The study analyzes key financial indicators such as profitability and liquidity to understand firms’ decisions to delist, noting that companies with weak financial health were more likely to opt for voluntary delisting. The findings underscore the importance for policymakers and investors to recognize the risks associated with delisting and to develop strategies to mitigate adverse effects during these disruptions. This comprehensive insight contributes to the limited literature on delisting in the Indian context and offers valuable guidance for stakeholders navigating this complex phenomenon.